A general and extensible framework for assessing change detection techniques - Negri, Rogério G. [UNESP]; Frery, Alejandro C. (Elsevier, 2023)
Change detection techniques play an essential role in Remote Sensing applications, such as environmental monitoring, governmental planning, and studies of areas affected by natural disasters. This fact makes the development of more accurate change detection techniques a constant challenge. However, the lack of public benchmarks available to analyze and compare the performance of change detection techniques hampers quantitative comparisons. In light of this reality, this study proposes and formalizes a novel framework for imagery dataset simulation. In contrast with other image simulation methods, images synthesized by the proposed method are explicitly designed to assess and compare change detection methods. The framework is extensible and general allowing, in particular, the use of both supervised and unsupervised change detection methods. As an application, we compare the performance of well-known algorithms to data sets that mimic what the Landsat 5 TM sensor observed over a forest area subjected to deforestation for agricultural purposes. The results support discussing the performance of methods and show the usefulness of the proposed framework. We provide the source codes in a public repository.
Keywords: Change detection; Classification assessment; Image simulation